Associations of the risk of lung cancer with serum 25-hydroxyvitamin D level and dietary vitamin D intake: A dose-response PRISMA meta-analysis. Issue 37 (September 2018) - Wei, Hu; Jing, Hu; Wei, Qian; Wei, Guo; Heng, Zhou
Abstract : Abstract: The associations of the risk of lung cancer with the vitamin D intake and serum level are controversial. We performed a comprehensive dose-response meta-analysis to evaluate the precise relationships between the above mentioned parameters. We performed a web search of the PubMed, Medline, and Embase databases to identify potential studies that evaluated the relationships between vitamin D intake or serum 25-hydroxyvitamin D (25([OH]D) levels and the risk of lung cancer on December 5, 2017. According to the inclusion and exclusive criteria, 16 studies were included in this meta-analysis. The pooled relative risks (RRs) with 95% confidence intervals (CIs) were used to assess the strength of the associations. A dose-response analysis was conducted to quantitate the relationship between the serum 25(OH)D or vitamin D intake and the risk of lung cancer. The pooled RR (highest level vs lowest level) showed that the serum 25(OH)D level was not associated with the risk of lung cancer (RR = 1.046, 95% CI = 0.945–1.159). A high vitamin D intake was inversely correlated with the lung cancer risk (RR = 0.854, 95% CI = 0.741–0.984). No significant dose-response relationship was observed between the serum 25(OH)D level and the lung cancer risk. The linearity model of the dose-response analysis indicated that with every 100 IU/day increase in vitamin D intake, the risk of lung cancer decreased by 2.4% (RR = 0.976, 95% CI = 0.957–0.995, P = .018). A high vitamin D intake provides limited protection against lung cancer carcinogenesis.